Ο εκδότης Ν. Π. Ιγγλέσης και το περιοδικό Εύα (1923-1924): Μια αφανής προσπάθεια ίδρυσης εκδοτικού ομίλου στην Ελλάδα κατά τον Μεσοπόλεμο - Delveroudi, Elisa Anna (The Gleaner, 2024)
Publisher N. P. Inglessis and the magazine Eva (1923-1924) Publisher of one French and five Greek-language publications, daily and weekly, during the 1920s, N. P. Inglessis has remained to this day a rather invisible case in the history of the Greek Press. Born in the late 1870s in Constantinople, he studied at the Chalki School of Commerce, and probably in London, and worked as an employee and then manager of the Bank of Athens before turning to publishing. My research in the Historical Archive of the National Bank of Greece provided biographical and financial material, which allows us to assume the origin of the funds that supported the turn in his professional life. His publications were short-lived, but pioneering and insightful, seeking to fill thematic gaps, and reach the interested audiences. His popular magazine Eva, presented in more detail here, addressed a large number of women readers and often popularized positions of the women’s movement, especially those related to work, spreading them to wider and lower social strata, who could not access the original collectives and theoretical discourses. Eva has probably worked as a model for similar publications, which circulated the following years in Greece. Accordingly, Inglessis’ Kinimatografos/Cinema, the first Greek magazine of its kind, dedicated to film, had also a clearly targeted readership, as well as his last and final attempt, Athlitika Chronika/Athletic Chronicles. Interestingly, N. P. Inglessis was the father of the first Greek film critic Iris Skaravaiou, indicating a path through which women could enter the journalist profession.